Lan ‘And’ Conjunction in Balinese - I Wayan Mawa; I Wayan Tama; I Wayan Sudiartha; Temaja, I Gede Bagus Wisnu Bayu (Cita konsultindo, 2023)
This research aimed to identify the conjunction of lan ‘and’ Balinese syntactic construction. Specifically, the connector of “and” was analyzed on its syntactic and semantic roles. The results show that the syntactical conjunction of “and” belongs to the coordinative connector, its relationship closely to the conjuncts or the constituents being connected; hence it cannot stand alone. This conjunction links two or more conjuncts such as words, phrases, clauses, and sentences. Its position is generally in front of the last conjunct that is being connected. “And” can correspond to several conjunctive adverbs in linking conjuncts. Semantically, the conjunction of “and” has semantic roles of the combination consisting of combination roles of sequence, collective, distributive, emphatic, terminative, and continuative. The conjuncts connected by “and” have semantic roles, such as the combination of pure, sequential, contrastive, evaluative, amplificative, pharasfrative, parallel, consequential, cause-effect, and leniency-result.